Inclusion in Stanford's list of top 2% researchers worldwide - Kyriakidis, Phaedon (My University, 2026)
Inclusion in the August 2024 data-update for "Updated science-wide author databases of standardized citation indicators" DOI: 10.17632/btchxktzyw.7 https://elsevier.digitalcommonsdata.com/datasets/btchxktzyw/7
Keywords: Worlds Top Scientists